HSP110 T17 simplifies and improves the microsatellite instability testing in patients with colorectal cancer. Issue 6 (1st February 2016) - Buhard, Olivier; Lagrange, Anaïs; Guilloux, Agathe; Colas, Chrystelle; Chouchène, Mouna; Wanherdrick, Kristell; Coulet, Florence; Guillerm, Erell; Dorard, Coralie; Marisa, Laetitia; Bokhari, Adem; Greene, Malorie; et al.
Abstract : Background: Every colorectal cancer (CRC) patient should be tested for microsatellite instability (MSI, a marker for defective DNA mismatch repair) as a first screen for Lynch syndrome (LS). In this study, we investigated whether it may be possible to improve the detection of MSI in CRC. We examined whether the HT17 DNA repeat (critical for correct splicing of the chaperone HSP110) might constitute a superior marker for diagnosis of the MSI phenotype in patients with CRC compared with the standard panel of markers (pentaplex). Methods: The HT17 polymorphism was analysed in germline DNA from 1037 multi-ethnic individuals. We assessed its sensitivity and specificity for detecting MSI in a multicentre, population-based cohort of 685 patients with CRC and an additional series of 70 patients with CRC considered to be at-risk of LS. All cases were screened earlier for MSI using pentaplex markers. Cases showing discordant HT17/pentaplex results were further examined for the expression of mismatch repair proteins. Results: HT17 status was analysed independently and blinded to previous results from pentaplex genotyping. HT17 showed no germline allelic variation outside a very narrow range. Compared with the pentaplex panel, HT17 showed better sensitivity (0.984 (95% CI 0.968 to 0.995) vs 0.951 (95% CI 0.925 to 0.972)) and similar specificity (0.997 (95% CI 0.989 to 1.000) for both) for the detection of MSI. Furthermore, HT17 alone correctly classified samples judged to be uncertain with the pentaplex panel and showed excellent ability to detect MSI in patients with LS. Conclusions: HT17 simplifies and improves the current standard molecular methods for detecting MSI in CRC.